Pesantren as a Community-Based Islamic Educational Institution - Rosita, Rosita; Ilyasin, Mukhamat; Muadin, Akhmad (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
This study aims to examine the role of Islamic boarding schools as community-based Islamic educational institutions and their contribution to the development of Islamic society in Indonesia. Using a literature review method, this study analyzes various secondary sources such as books, scientific articles, and national and international journals that are relevant to the topic. The results of the study indicate that Islamic boarding schools have a strategic role in forming a generation of Muslims with noble character and broad insight. Islamic boarding schools do not only focus on teaching religious knowledge, but also instill social, cultural, and life skills values ​​in their students. In facing the challenges of modernity and globalization, Islamic boarding schools are required to integrate general knowledge and technology into the curriculum without eliminating their Islamic identity. The efforts of Islamic boarding schools in realizing community-based Islamic education include the application of balance between relationships with Allah (hablum minallah) and relationships with fellow human beings (hablum minannas), as well as the application of social values ​​in the Qur'an as a guideline for community life. Islamic boarding schools are recognized as an important part of the national education system, which is able to become an agent of social change through community-based education.